2014
DOI: 10.1517/17425255.2014.967679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pharmaceutical PEGylation on drug metabolism and its clinical concerns

Abstract: PEGylation is an effective approach to potentiate drugs with undesirable properties. Currently, PEGylation has penetrated into every field of pharmaceutical practice, involving biomacromolecules, small drugs and drug delivery systems. Efficacy enhancement is attained through modification of the pharmacokinetics and toxicity profiles of parent drugs. As a result of PEGylation, the drugs tend to display enhanced solubility, prolonged circulatory time and reduced immunogenicity/antigenicity. The bottleneck of PEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 71 publications
1
56
0
Order By: Relevance
“…The relatively short duration of our study could contribute to this finding, as it has been reported that more patients on LB03002 treatment developed anti-rhGH antibody during the second year of the study vs the first year (12). Additionally, pegylated proteins/drugs usually have low immunogenicity/antigenicity (25, 26). …”
Section: Discussionmentioning
confidence: 99%
“…The relatively short duration of our study could contribute to this finding, as it has been reported that more patients on LB03002 treatment developed anti-rhGH antibody during the second year of the study vs the first year (12). Additionally, pegylated proteins/drugs usually have low immunogenicity/antigenicity (25, 26). …”
Section: Discussionmentioning
confidence: 99%
“…In principle, a sub-library of m macrocycles and sub-library of n squaraine scaffolds can be mixed in parallel combinatorial fashion to create a library of m x n fluorescent probes, each with incremental structural changes such as ligand copy number, linker distance, linker flexibility, and degree of PEGylation to control biodistribution. 30, 31 The macrocycle threading process that is the basis of the pre-assembly method is shown in Figure 2 and we call it Synthavidin (Synthetic Avidin) technology. 32 The macrocycle is a water-soluble tetralactam with anthracene sidewalls, and previous studies have shown that it can be threaded by a PEGylated squaraine dye to give a highly stable complex with nanomolar dissociation constant.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2013, 15 GPCR-related drugs were approved as new chemical entities (NCEs) in 31 months, with exclusions as specified in Table 2. Among these NCEs, naloxegol 12 is a derivative of a known opioid receptor (OR) antagonist that is covalently linked to a short polyethylene glycol (PEG) chain to prevent its intestinal absorption; thus, it selectively blocks opiate receptors in the gut to prevent side effects of systemic opiates [5]. Several of these new drugs treat sleep conditions: suvorexant 10 blocks two subtypes of the orexin receptor, which is a first drug in that category [6].…”
Section: Introductionmentioning
confidence: 99%